2017
DOI: 10.3897/zookeys.695.13360
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of Trichomycterus areolatus Valenciennes, 1846 from southern Chilean rivers using a truss-based system (Siluriformes, Trichomycteridae)

Abstract: Trichomycterus areolatus Valenciennes, 1846 is a small endemic catfish inhabiting the Andean river basins of Chile. In this study, the morphological variability of three T. areolatus populations, collected in two river basins from southern Chile, was assessed with multivariate analyses, including principal component analysis (PCA) and discriminant function analysis (DFA). It is hypothesized that populations must segregate morphologically from each other based on the river basin that they were sampled from, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Therefore, in a geographically vast country like India having a number of isolated rivers, there is more possibility of variations among sh populations, which can be clearly depicted in the present study. The present study is in agreement with previous studies conducted with the same objective of detecting intraspecies morphological differences in other cyprinids [69][70][71][72] and non-cyprinids [49,73,74] Though, there are also reports on low morphometric divergences despite of geographically isolated populations [75]. Hence, patterns of morphological structure in shes differed between river basins/rivers/river stretches.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, in a geographically vast country like India having a number of isolated rivers, there is more possibility of variations among sh populations, which can be clearly depicted in the present study. The present study is in agreement with previous studies conducted with the same objective of detecting intraspecies morphological differences in other cyprinids [69][70][71][72] and non-cyprinids [49,73,74] Though, there are also reports on low morphometric divergences despite of geographically isolated populations [75]. Hence, patterns of morphological structure in shes differed between river basins/rivers/river stretches.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, fish skin or fillet color and pearl quality traits (e.g., color, luster, and complexion), which are traditionally recorded as categorical traits, can now be recorded as highly reliable continuous quantitative traits based on ultraviolet-vis spectrophotometry measurements (e.g., Urban et al., 2013; Kustrin and Morton, 2015). The performance of MVS and traditional color measurements has been compared with Atlantic salmon, rainbow trout, and pearls with spectral patterns produced by MSV more representative and consistent of the real color (Yagiz et al., 2009; Mamangkey et al., 2010; Colihueque et al., 2011, 2017; Toyota and Nakauchi, 2013), which will ultimately improve genomic selection predictions.…”
Section: Pathway For Incorporation Of Genomic Selection Into Aquacultmentioning
confidence: 99%
“…Furthermore, the transient behavior of mackerel may be conducive to the conglomeration of fish from different populations. Colihueque et al [26] found that the morphometric variations of Trichomycterus areolatus Valenciennes 1846 might be associated with variations in habitat [27].…”
Section: Resultsmentioning
confidence: 99%